Gambaran Kadar Elektrolit Darah (Natrium, Kalium, Klorida) Pada Pasien Balita Usia 0-5 Tahun dengan Diare Akut Di RSAB Harapan Kita Jakarta - Nurdiani, Catu Umirestu; Sari, Indah Novitha Fitria; Nugroho, Heru Purwanto (Universitas Mohammad Husni Thamrin, 2024)
Diarrhea is an increase in the frequency of defecation, which is characterized by a stool consistency that is thinner than usual. Viruses, bacteria, and parasites can cause diarrhea. Diarrhea is the second most common cause of death in toddlers. The main cause of death in toddler diarrhea is severe dehydration due to excessive fluid loss. Laboratory tests on diarrhea patients include blood electrolyte tests including sodium, potassium, and chloride. This quantitative research is conducted with secondary data obtained from medical records and then processed. The study was conducted on all 64 patients aged 0-5 years with acute diarrhea at RSAB Harapan Kita. The results showed that based on gender, it was dominated by males with the highest abnormal electrolyte levels in chloride at 34 people (53.13%) with the lowest chloride value of 81 mmol/L and the highest chloride value of 125 mmol/L. Based on age, most diarrhea patients were found to occur in toddlers (1-5 years) with the highest abnormal electrolyte levels in chloride at 29 people (45.31%) with the lowest chloride value of 81 mmol/L and the highest chloride value of 114 mmol. /L. The research that has been carried out can conclude that in patients suffering from diarrhea, the average value of the patient's sodium and potassium levels is normal, while the chloride levels are high. It is hoped that it is important for parents of diarrhea sufferers to always maintain a clean environment to prevent diarrhea and immediately go to the nearest doctor or hospital when the body shows symptoms such as fever and continuous defecation. Keywords: Diarrhea, Sodium, Potassium, Chloride